PhET-Aided Blended Problem Based Learning Rotation Model to Improve Junior High School Students' Higher-Order Thinking Skills - Rai Sujanem; K. Suma; P. Yasa; I. Yuliana; P. Sarini (Jurnal Penelitian Pendidikan IPA, 2026)
To face global challenges, students need to be equipped with Higher-Order Thinking  Skills (HOTS). This study aimed at analyzing the positive contributes of the Physics Education and Technology (PhET)-aided Blended-Problem-Based Learning Rotation (BPBLR) model in improving HOTS and describing student responses to the PhET-aided BPBLR model. This study involved 98 seventh grade students in Singaraja who were spread across 3 experimental groups, namely 31, 33, 34, and without control group. This research design was a pre-test and post-test group design. The collected data were analyzed using paired-test, normalized gain (N-gain), and ANOVA. The results of the Paired-Test showed that there was a significant difference in students' HOTS achievement with the PhET-aided BPBLR Model between pretest and posttest for three groups at p < 0.05. The average N-gain HOTS values in each group are: 0.46, 0.45, and 0.46, which are in the moderate category. The ANOVA test results show that the average N-gain values of the three groups is consistent at p < 0.05. Student responses are in very high category. Thus, the use of the PhET-aided BPBLR model contributes positively to improve students' HOTS, and student responses are in very high category.